Molecular Mechanisms and Risk Factors for the Pathogenesis of Hydrocephalus - Li, Jingwen; Zhang, Xinjie; Guo, Jian; Yu, Chen; Yang, Jun (Frontiers in Genetics, 2022)
Hydrocephalus is a neurological condition due to aberrant circulation and/or obstruction of cerebrospinal fluid (CSF) flow with consequent enlargement of cerebral ventricular cavities. However, it is noticed that a lot of patients may still go through symptomatic progression despite standard shunting procedures, which suggests that hydrocephalus is far more complicated than a simple CSF circulative/obstructive disorder. Increasing studies indicated that genetic factors may play a fundamental role in the pathogenesis of hydrocephalus. Although the genetic research of hydrocephalus in humans is limited, many genetic loci of hydrocephalus have been defined in animal models. In general, the molecular abnormalities involved in the pathogenesis of hydrocephalus may relate to brain development and ependymal cell dysfunction, apoptosis, inflammation, free radical, blood flow and cerebral metabolism, and others. However, intensive studies have indicated that the molecular abnormalities relevant to aberrant cerebral glymphatic drainage turn into an attractive subject in the CSF circulation disorder. Furthermore, the prevalent risk factors could facilitate the development of hydrocephalus. In this review, we elicit the possible fundamental molecular mechanisms and facilitating risk factors involved in the pathogenesis of hydrocephalus and aim to widen the diagnosis and therapeutic strategies for hydrocephalus management. Such knowledge could be used to improve patient care in different ways, such as early precise diagnosis and effective therapeutic regimens.